1984
DOI: 10.2307/1590235
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo Studies with an Avian Reovirus Derived from a Temperature-Sensitive Mutant Clone

Abstract: A temperature-sensitive (ts) mutant of avian reovirus isolate Maine 1-203 was obtained at 41 C. The 19th passage of this mutant (ts 19) was utilized for in vitro studies comparing its replication in macrophage cultures with that of its parent strain and an apathogenic S1133 virus. In vivo studies were initiated to determine the ts mutant's pathogenicity for day-old chicks, safety and protective levels for 6-day-old chicks, and interference with Marek's disease, Newcastle, and infectious bronchitis vaccinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…We have previously shown that the S1 genome segment, which encodes the p10 fusion protein of ARV, contributes approximately 60% of the embryo pathogenic potential of ARV-176 (8). In view of the ability of various strains of ARV to infect macrophages in vivo and under culture conditions (12,19,23,38), the transient immunosuppression that accompanies ARV-176 infection (25), and the central role of the macrophage in orchestrating the early immune response to virus infection, it is conceivable that the preferential infection of macrophages by ARV-176 in FIG. 6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that the S1 genome segment, which encodes the p10 fusion protein of ARV, contributes approximately 60% of the embryo pathogenic potential of ARV-176 (8). In view of the ability of various strains of ARV to infect macrophages in vivo and under culture conditions (12,19,23,38), the transient immunosuppression that accompanies ARV-176 infection (25), and the central role of the macrophage in orchestrating the early immune response to virus infection, it is conceivable that the preferential infection of macrophages by ARV-176 in FIG. 6.…”
Section: Discussionmentioning
confidence: 99%
“…However, this would need to be directly evaluated in vivo, since the macrophage infection propensity of ARV-176 has never been evaluated in infected animals and the relationship between ARV macrophage infection and virus pathogenicity remains unclear (12,38). Similar confusion regarding the correlation between virus pathogenicity and macrophage infection exists with other viruses, such as herpes simplex virus (10,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avian reovirus has also been reported to replicate in chicken bone marrow-derived macrophages (Bülow & Klasen, 1983) and in blood monocyte cultures (Haffer, 1984) which might explain, in part, the reason for the observed immunosuppression. However, perusal of literature did not reveal any information about the interaction of avian reovirus with the different subsets of chicken lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Οι ρεοϊοί των πτηνών πολλαπλασιάζονται επίσης σε κυτταροκαλλιέργειες από μακροφάγα κύτταρα του μυελού των οστών ή μακροφάγα που προέρχονται από μονοκύτταρα του αίματος (Bulow & Klasen, 1983" Haffer, 1984.…”
Section: καλλιεργητικοί χαρακτήρες και κυτταροπαθογόνος δράση του ιούunclassified